A business canvas model on vermicomposting process: Key insights onto technological and economical aspects. (June 2022) - Thirunavukkarasu, Arunachalam; Nithya, Rajarathinam; Kumar, Subbian Makesh; Priyadharshini, Venkatachalam; Kumar, Balakrishnan Prem; Premnath, Paneerselvam; Sivashankar, Raja; Sathya, Arunachalam Bose
Abstract: In the present study, a pilot-scaled size (0.5 tons) of the vermicomposting process was adopted using the vegetable waste as substrate for the earthworm, Eisenia fetida . The harvested vermicompost was technically assessed for its stability, maturity and other physicochemical parameters. Further, the study has provided a comprehensive examination of the cost economics of the vermicomposting along with the SWOT analysis. Key insights on the cost-benefit breakdown and economic analysis were discussed and a net profit ratio of 139.5 % and 134.6 % was figured for the 2nd and 3rd harvesting years respectively. With 15 % of the discounting rate, the Net Present Worth (NPW) of cost and benefit were computed as Rs.7.63 lakh and Rs.11.94 lakh respectively and hence the Benefit-Cost Ratio (BCR) was observed as 1.56. With this superior BCR, the present study is presenting a technologically feasible and economically successful business model on vermicomposting for the young entrepreneurs and start-up aspirants. Graphical abstract: Unlabelled Image Highlights: A pilot-scale-sized (0.5 ton) vermicompost process was implemented using E. fetida . A comprehensive examination on the cost economics and SWOT analysis was presented. Presented a sustainable business canvas model with high BCR to start-up aspirants